A PHONEMIC CONTRASTIVE ANALYSIS OF TIV AND ENGLISH SEGMENTALS - D.T., WAYA; T., KWAMBEHAR S. (Innovare Journal of Social Sciences, 2014)
A contrastive approach enables one to examine the differences that exist between languages and the obvious challenges poses to the learner of a target language. It is then that possible right approaches to overcoming possible challenges would be employed. This paper delves into a contrastive analysis of the Tiv and English languages with particular reference to the segmental features of both languages. The study shows that Tiv language has more phonemic consonants than English language. However, both languages exhibit equal number of vowels except that there are some vowels. Those in Tiv which are not found in English are /a/ and /o/. The ones in English that are not present in Tiv are /âˆ‚/ and /Ã¦/. Also, tone plays an important role in the use of vowels in Tiv, such that a vowel sound can give different meanings to different words Â and can only be distinguish in orthographic form through tone marking. English language does not mark vowel differences in tone but intonation. A study of this nature charts the way forward into providing remedial measures to Tiv learners of English as L2 or target language. Key Words: Contrastive analysis, phonemic, segmental, second language, First language, TivÂ